Atypical Glandular Cell Suggestive of Adenocarcinoma In Situ on Pap Smear Examination - Hamidiyah, Silpi; Azmi, Sabrina (Jurnal Ners, 2025)
Introduction: Atypical Glandular Cells (AGC) on Pap smear is a finding that requires further evaluation, as it may indicate precancerous lesions such as adenocarcinoma in situ (AIS) or invasive adenocarcinoma. This case discusses a 45-year-old woman with postcoital spotting, diagnosed with AGC suggesting AIS and a focus of adenocarcinoma. Case Report: The patient presented to the clinic with postcoital spotting over the past two weeks. Cervical examination revealed a mass on the cervix from the 11 o’clock to 4 o’clock position. A Pap smear revealed AGC suggesting AIS. The patient subsequently underwent colposcopy and biopsy, which confirmed adenocarcinoma in situ with a focus of invasive adenocarcinoma. Discussion: Atypical Glandular Cells on Pap smear carry a significant risk of cervical neoplasia. Further evaluation with colposcopy and biopsy is crucial for accurate diagnosis. In this case, the finding of adenocarcinoma in situ with a focus of invasive adenocarcinoma highlights the need for aggressive management, such as hysterectomy, to prevent progression to fully invasive cervical cancer. Management with radical hysterectomy was recommended to prevent further progression to invasive cancer. This procedure aimed to remove the lesion completely and prevent recurrence. Conclusion: Detection of AGC suggesting AIS requires immediate investigation for proper diagnosis and management. Radical hysterectomy may be an effective treatment option to prevent further progression and improve the patient’s prognosis. Keywords: AGC, AIS, pap smear.